Investigation of H-mode density limit in mixed protium–deuterium plasmas at JET with ITER-like wall - A. Huber; G. Sergienko; M. Groth; D. Keeling; M. Wischmeier; D. Douai; E. Lerche; C. Perez von Thun; S. Brezinsek; V. Huber; A. Boboc; M. Brix; et al. (Nuclear Materials and Energy)
Analysis of comparable discharges fuelled by either deuterium or protium reveals a clear relationship between the isotope mass and the H-mode density limit. Notably, the density limit is significantly lower in protium, showing a reduction of up to 35 % compared to identical deuterium plasma conditions. Within mixed H-mode density limit (HDL) plasmas, the maximum achievable density, or H-mode density limit, decreases with increasing protium concentration, denoted as cH. For instance, the highest corresponding maximum Greenwald fraction (fGW) of about 1.02 was observed in the pulse with the lowest cH value of 4.4 %. This fGW decreases to 0.96 at cH = 48 %. The average atomic mass, A¯, of the plasma species decreases in these pulses from the value of 1.96 (cH = 4.4 %) down to 1.52 (cH = 48 %). Interestingly, the maximum achievable density appears to be largely unaffected by the applied power value, regardless of whether deuterium or protium is used, as well as under mixed H/D fuelling conditions.Additionally, the measured Greenwald fractions are agreed with a heuristic model based on the SOL pressure threshold of an MHD instability, as proposed by Goldston. This comparison, especially concerning the model’s dependence on isotopic mass, shows full consistency between the measured and predicted Greenwald fractions.